Studi Kasus Pengukuran Implementasi Information Assurance untuk e-Government menggunakan Metode Goal Question Metric - Rio Guntur Utomo (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2021)
Internet technology has been used in various fields, such as business, government, health, and education, including government, which is often called electronic government or eGovernment. Indonesia is one of the countries that has implemented eGovernment. In its implementation, eGovernment services must always be available, and every threat to information and systems must receive attention to ensure business continuity in the event of an incident. Therefore, in implementing eGovernment, information assurance (IA) must be considered. To determine the extent to which IA implementation status to protect eGovernment services in Indonesia, it is necessary to measure the implementation using an instrument. The measurement instrument is developed from the IA framework using the Goal Question Metric (GQM) method. The results of the measurement show that the status of implementing IA for e Government in Indonesia is still not satisfactory